Dual echo z-shimmed proton resonance frequency-shift MR thermometry near metallic ablation probes: Technique and temperature precision - Zhang, Yuxin (Magn Reson Med, 2017)
PURPOSE: To improve the precision of proton resonance frequency-shift MR thermometry near ablation probes, by recovering near-probe image signals that are typically lost due to magnetic susceptibility-induced field distortions. METHODS: A dual-echo gradient-recalled echo sequence was implemented, in which the first echo was under- or over-refocused in the slice dimension to recover image signal and temperature precision near a probe, and the second echo was fully-refocused to obtain image signal everywhere else in the slice. A penalized maximum likelihood algorithm was implemented to estimate a single temperature map from both echoes. Agar phantom and ex vivo experiments with and without microwave heating at 3 Tesla evaluated how much temperature precision was improved near a microwave ablator compared to a conventional single-echo scan as a function of slice and needle orientation in the magnet. RESULTS: The number of near-probe voxels with temperature standard deviation σ > 1 °C was decreased by 51% in the phantom experiment, averaged across orientations, and by 31% in the pork. Temperature maps near the probe were more smoother and more complete in all orientations. CONCLUSION: Dual echo z-shimmed temperature imaging can recover image signal for more precise temperature mapping near metallic ablation probes.